Antimicrobial effects of mustard oil-containing plants against oral pathogens: an in vitro study - Eichel, Vanessa; Schüller, Anne; Biehler, Klaus; Al-Ahmad, Ali; Frank, Uwe (BMC complementary medicine and therapies, 2020)
The present study examines the antimicrobial activity of nasturtium herb (Tropaeoli maji herba) and horseradish root (Armoraciae rusticanae radix) against clinically important oral bacterial pathogens involved in periodontitis, gingivitis, pulpitis, implantitis and other infectious diseases.
Gesehen am 16.09.2020